Extratos etanólicos dos resíduos da manga como antioxidante em rações contendo diferentes fontes lipídicas para poedeiras comerciais em postura - Lima, Paula Joyce Delmiro de Oliveira (2021)
The objective was to evaluate the inclusion of the ethanolic extract of the mango seed (EECar) and of the mango peel (EECas) as antioxidant on laying hens fed with different sources of fat in the diet on performance and internal and external quality of fresh eggs, the lipid stability (TBARS) of fresh and stored eggs, the internal and external quality characteristics of the eggs and the indicators of egg foam formation and stability of the eggs submitted to different conditions temperature and storage time. Two experiments were conducted using 240 Hy-Line Brown laying hens in the first experiment and 360 in the second experiment, both at 60 weeks of age. In the first experiment, the birds were distributed in a completely randomized design with a 2x3 factorial, with two levels of EECar (0 mg/kg and 1000 mg/kg) and 3 sources of lipids (soybean oil, sunflower oil and crude glycerin ), totaling six treatments and five repetitions of eight birds each. For the second experiment the layers were distributed in a completely randomized design with a 3x3 factorial scheme, three levels of EECas (0 mg/kg, 500 mg/kg and 1000 mg/kg) and 3 sources of lipids (soybean oil, sunflower and crude glycerin), total nine treatments and five repetitions of eight birds each. The treatments of the first experiment consisted of six rations: T1 – ration with soy oil without inclusion of EECar; T2 - ration with sunflower oil without inclusion of EECar; T3 – ration with crude glycerin without inclusion of EECar; T4 – ration with soy oil and 1000 mg/kg of EECar; T5 - ration with sunflower oil and 1000 mg/kg of EECar; T6 - ration with crude glycerin and 1000 mg/kg of EECar. The treatments used in the second experiment consisted of: T1 – ration with soy oil without inclusion of EECas; T2 - ration with sunflower oil without inclusion of EECas; T3 – ration with crude glycerin without inclusion of EECas; T4 – ration with soy oil and 500 mg/kg of EECas; T5 - ration with sunflower oil and 500 mg/kg of EECas; T6 - ration with crude glycerin and 500 mg/kg of EECas; T7 – ration with soy oil and 1000 mg/kg of EECas; T8 - ration with sunflower oil and 1000 mg/kg of EECas; T9 - ration with crude glycerin and 1000 mg/kg of EECas. The total experimental period was 126 days, divided into 6 periods of 21 days. The use of the ethanol extract from the seed and mango peel in laying hens did not significantly influence any of the variables evaluated for egg performance and quality. Regarding the lipid stability of the egg yolk, there was a significant effect of the inclusion of EECar and EECas only on the lipid oxidation that reduced with the inclusion in fresh and stored eggs. Among the lipid sources, it was observed that the use of crude glycerin in the diet promoted an increase in the albumen pH and lipid oxidation in the yolk of fresh and stored eggs. There was no significant interaction between the factors on the variables studied in fresh eggs, however, as for stored eggs, it was observed that storage in a refrigerated environment promoted better results of internal egg quality. Thus, the addition of ethanol extracts from mango reduces lipid oxidation in the yolks, anyhow of the lipid source and type of storage, and crude glycerin as a lipid source increases the albumen's pH and the lipid stability of the egg yolk.